2014
DOI: 10.1016/j.jcis.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Decisive influence of colloidal suspension conductivity during electrophoretic impregnation of porous anodic film supported on 1050 aluminium substrate

Abstract: The present paper studies the influence of suspension conductivity on the electrophoretic deposition (EPD) of nanoparticles inside a porous anodic aluminium oxide film. It is shown that an increase in the suspension's conductivity enhances impregnation of the anodic film by the nanoparticles. Two mechanisms are seen to promote the migration of particles into the pores. Indeed an increase in the suspension conductivity leads on the one hand to a strengthening of the electric field in the anodic film and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Complementarily, they showed that faster deposition was obtained under higher electric field but resulted in the formation of nanotubules. Similar conclusions were attained by Fori et al, , who successfully performed the electrophoretic deposition on the barrier layer of anodized aluminum using SiO 2 colloidal dispersion in isopropyl alcohol (IPA). They emphasized that higher electric field and dispersion conductivity improves the impregnation and flocculation of the nanoparticles in the pores.…”
Section: Introductionsupporting
confidence: 80%
“…Complementarily, they showed that faster deposition was obtained under higher electric field but resulted in the formation of nanotubules. Similar conclusions were attained by Fori et al, , who successfully performed the electrophoretic deposition on the barrier layer of anodized aluminum using SiO 2 colloidal dispersion in isopropyl alcohol (IPA). They emphasized that higher electric field and dispersion conductivity improves the impregnation and flocculation of the nanoparticles in the pores.…”
Section: Introductionsupporting
confidence: 80%
“…Electrophoresis approaches using porous substrates based on anodic aluminium oxide (AAO) [20][21][22] or graphite [23] had been already reported with using non-aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…Fori et al [18,19] responded to this issue by using an organic based dispersion of SiO 2 particles, leading to complete filling of the pores, thus successfully avoiding side reactions such as solvent electrolysis. Despite the difficulties encountered in using an aqueous medium for EDP, Kusdianto et al [20] reported the potential to fill pores of less than 1µm in length using a pulsed electric field to limit water splitting, while Escobar and al.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Fori et al [19] have already shown (although in organic media), that to obtain the migration of particles into the pores it was necessary to increase the conductivity of the solution: the interaction between particles and pore walls is reduced thanks to the electric double-layer compression of both the pore/electrolyte and the particle/electrolyte interfaces. They also demonstrated that increasing conductivity of the dispersion led to focusing the electric field on the anodic film region, improving particle impregnation throughout the anodic film.…”
Section: Influence Of Dispersion Conductivity On the Threshold Potentialmentioning
confidence: 99%